2014
DOI: 10.1111/bij.12350
|View full text |Cite
|
Sign up to set email alerts
|

Ant dominance hierarchy determines the nested pattern in ant-plant networks

Abstract: Extrafloral nectar (EFN) is a predictable and renewable resource for many ant colonies, and different ant species compete strongly to obtain and monopolize this highly nutritious food resource. Despite the importance of competition in structuring patterns of ant–plant interactions, this biological mechanism has been largely ignored in studies involving ant–plant networks. In this study we investigate the role of ant dominance hierarchy in structuring an ecological network involving ants and EFN‐bearing plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 66 publications
1
38
2
3
Order By: Relevance
“…Although they encompass only 1% of the ant species recorded in the region [36], they are over-represented in the multilayer network (> 50% of records). Previous studies carried out in distinct habitats suggest that the cores of ant-EFN and ant-honeydew networks are composed by competitively superior ant species [25,31]. In fact, Camponotus crassus and Camponotus rufipes are numerically dominant and aggressive ants, which are considered truly trophobiont and plant mutualists in cerrado [69] and campo rupestre [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they encompass only 1% of the ant species recorded in the region [36], they are over-represented in the multilayer network (> 50% of records). Previous studies carried out in distinct habitats suggest that the cores of ant-EFN and ant-honeydew networks are composed by competitively superior ant species [25,31]. In fact, Camponotus crassus and Camponotus rufipes are numerically dominant and aggressive ants, which are considered truly trophobiont and plant mutualists in cerrado [69] and campo rupestre [70].…”
Section: Discussionmentioning
confidence: 99%
“…In ant-plant networks specifically, is known that a few central ant species form a core that strongly influences the structure of the entire community [28]; this is especially true in generalized ant-EFN networks compared to those involving specialized myrmecophytic plants [29]. This core of central ant species is consistent in space [28] and time [30], and consists mostly of dominant species displaying high recruitment rates and strong territoriality [31]. …”
Section: Introductionmentioning
confidence: 99%
“…La efectividad de la defensa contra herbívoros que pueden aportar las hormigas asociadas a plantas con NEFs puede ser muy variable, ya que se encuentran involucradas desde asociaciones obligadas hasta asociaciones facultativas generalistas (Giusto et al, 2001). Asimismo, los beneficios para las plantas en términos de adecuación pueden estar influenciados por diversos factores tales como: comportamientos defensivos de las hormigas que las visitan, abundancia, presión de herbívoros y balance costo-beneficio (Bronstein, 1994;Rico-Gray y Oliveira, 2007;Dáttilo et al, 2014).…”
Section: Las Interacciones Planta-hormiga-herbívorounclassified
“…These results suggest that species phylogeny may not be the most important factor in partner selection, either for ants or for partners. Partner selection by ants could be driven by other factors not necessarily shared by related species, such as phenology (Rico-Gray et al, 2012), abundance (Chamberlain et al, 2010;Dáttilo et al, 2014b), body size (Chamberlain & Holland, 2009b), ant dominance hierarchies (Dáttilo et al, 2014a) and abiotic factors (Rico-Gray et al, 2012), which have been demonstrated to be good predictors of the structure of ant-EFN interaction networks. Moreover, ant visitation to FN was shown to depend on seasonality (Santos et al, 2014), and the presence of floral barriers and repellents, which were in turn independent of plant phylogeny (Junker et al, 2011).…”
Section: Do Different Myrmecophilic Partners Differ In the Taxonomic mentioning
confidence: 99%